(untitled) (Revista de Ciências Agroveterinárias, 2017)
quality and, therefore, it loses competitiveness. Thus, the Ministry of Agriculture, Livestock and Supply, published on December 30, 2011, the Normative Instruction 62, in which fixed values for the physical and chemical parameters, somatic cell counts (SCC), composition and total bacterial counts (TBC) as well proposing controlling inhibitors and antibiotic residues in milk. Due to the implementation of this rule, the aim of this work was to evaluate the quality of raw milk produced on the properties in the semiarid region of Minas Gerais state as well as the profile of the installations and dairy farmers. We collected 92 samples of raw milk and sent them for analysis in milk clinical and industry laboratory. Physical and chemical analysis, somatic cell count, total bacterial count and antibiotic residue test were performed. The data relating to the profile of producers, sanitary conditions and the types of buildings were obtained by means of questionnaires and the data was presented as a percentage. The values of the physical-chemical properties were submitted to the chi-square test and it was found that they are consistent with current legislation. The SCC parameters, TBC and cryoscopic index showed values above those allowed by law. The lack of milk cooling was the parameter with the highest non-compliance with respect to IN 62.